Ceramic tile product and preparation method thereof

By polishing and drawing on the base layer of the ceramic tile substrate to form micropore or crack structures, and embed decorative layers, the problem of poor durability of decorative layers of ceramic tile products is solved, and more stable and economical production is achieved process.

CN119504246APending Publication Date: 2025-02-25FOSHAN TAOZHE CERAMIC TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510089880.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The decorative layers of existing ceramic tile products have poor durability, are prone to wrinkles and fall off, and are complex in production processes and high in cost.

Method used

By polishing and drawing the base layer of the ceramic tile substrate, a base layer with a water absorption rate of 0.1% to 6%, and micropores or cracks with diameters of 10 to 3000 μm are laid on the surface, and the decorative layer covers the surface. and embedded in it to form a decorative layer with a stable structure.

Benefits of technology

It improves the durability of the decorative layer, avoids wrinkles and falls, and simplifies production processes and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504246A_ABST
    Figure CN119504246A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic products, in particular to a ceramic tile product and a preparation method thereof.The ceramic tile product comprises a ceramic tile base body, a decorative pattern layer and a protective layer which are sequentially stacked from bottom to top, and is characterized in that the ceramic tile base body comprises a base face layer and a base layer which are stacked up and down, the water absorption rate of the base face layer is 0.1%-6%, and the water absorption rate of the base layer is 0.1%-6%; the thickness of the base surface layer is 0.1 to 3 mm; a plurality of micropores or cracks are distributed on the surface of the base surface layer, and the decorative pattern layer covers the base surface layer and is embedded into the micropores or cracks. The decorative pattern layer and the base surface layer are organically combined together, so that the decorative pattern layer is very stable and not prone to falling off, and meanwhile the decorative pattern layer has the mild and soft texture of natural materials and is very close to the texture of the natural materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic products, in particular to a ceramic brick product and a preparation method thereof. Background Art

[0002] The pattern and texture of natural stone are natural and smooth, and the touch is gentle and simple. It has always been the first choice for decoration materials in high-end places. However, natural stone resources are limited and expensive, and it is not suitable for large-scale use. Therefore, people have been trying to use ceramic technology to prepare highly simulated ceramic tile products to replace natural stone. In the existing ceramic tile technology, the preparation method of imitating natural material patterns is usually applied on the surface of the ceramic body to produce simulated ceramic tiles. On the one hand, the ceramic body will shrink and deform during the firing process, resulting in texture docking deviation when multiple continuous bricks are laid; and the colors of natural materials are extremely rich and varied, and ceramic colorants fired at high temperatures cannot fully meet the color requirements. In order to solve the above technical problems, people use a technical method of inkjet printing on vitrified ceramic materials, such as the application number 202180022846.3 and the name "Method for manufacturing rounded corner tiles and rounded corner tiles" The Chinese patent document with application number 2016104819891 and titled “A method for preparing ceramic inkjet and a method for applying ceramic inkjet” discloses a technical solution. However, in the above-mentioned technology, the ink is quickly cured under UV or EB radiation, so that the ink can only remain on the surface of the ceramic material, which makes the adhesion between the ink and the surface of the ceramic material small. After a long time, the decorative layer formed by the ink is easy to wrinkle and fall off, and the durability is poor; the Chinese patent document with application number 202211619015.7 and titled “A method for preparing an inkjet-printed non-fired decorative lightweight ceramic plate and its preparation method” discloses that a sealing primer and a white primer are first sprayed on a ceramic tile substrate, and then a diffusion-proof water-based paint is sprayed, and then a pattern is sprayed with an inkjet printer equipped with water-based inorganic color ink. This method is not only complicated in process and high in cost, but also has the problem that the decorative layer can only remain on the surface of the ceramic material, and the decorative layer is easy to wrinkle, fall off, and has poor durability. Summary of the invention

[0003] The object of the present invention is to solve the above-mentioned problems and shortcomings, and to provide a ceramic tile product and a preparation method thereof, wherein the decorative layer is organically combined with the base layer by making the water absorption rate of the base layer 0.1% to 6% and having a plurality of micropores or cracks with a diameter of 10 to 3000 μm on the surface, so as to form a structurally stable decorative layer, thereby greatly improving the durability of the decorative layer.

[0004] The technical solution of the present invention is implemented as follows: a ceramic tile product, including a ceramic tile substrate, a decorative layer and a protective layer stacked in sequence from bottom to top, wherein the ceramic tile substrate includes a base surface layer and a base layer stacked up and down, the base surface layer has a water absorption rate of 0.1% to 6%, the base layer has a water absorption rate of 0.01% to 7%, and the base surface layer has a thickness of 0.1 to 3 mm; the surface of the base surface layer is provided with a plurality of micropores or cracks with a diameter of 10 to 3000 μm, and the decorative layer covers the base surface layer and is embedded in the micropores or cracks.

[0005] Furthermore, the surface of the base surface layer is also provided with a serrated texture.

[0006] Furthermore, a bevel portion is provided at the edge of the ceramic tile substrate, and the bevel portion is located on the base surface layer.

[0007] The present invention also provides a method for preparing the above-mentioned ceramic tile products, comprising the following steps: S1: selecting fired ceramic materials as ceramic tile substrates; S2: using sandpaper or a grinding wheel to grind and brush the surface of the ceramic tile substrate to open the micropores or cracks on the surface of the ceramic tile substrate; S3: using ceramic ink to inkjet print on the surface of the ceramic tile substrate to form a decorative layer; S4: applying a protective layer with a thickness of 5 to 300 μm on the surface of the decorative layer; its characteristics are: the ceramic tile substrate has a base surface layer and a base layer, the water absorption rate of the base surface layer is 0.1% to 6%, and the thickness is 0.1 to 3 mm; the water absorption rate of the base layer is 0.01% to 7%.

[0008] Furthermore, the coating used for the protective layer is a coating that can be cured by EB curing technology. After the protective layer coating is applied to the decorative layer by spraying or roller brushing, the protective layer coating is cured by EB curing technology to form a protective layer. The operating process conditions of the EB curing technology are: the energy of the electron accelerator is 20 to 100 KeV, and the curing time is 0.1 to 5 s.

[0009] Furthermore, the coating used for the protective layer is an organic hybrid nano-silica sol coating or an organic hybrid nano-aluminum sol coating. After the protective layer coating is applied to the decorative layer by spraying or roller brushing, the protective layer coating is cured by heating and drying to form a protective layer. The heating and drying curing process conditions are: temperature 80-200°C, drying time 5-30 minutes.

[0010] Furthermore, travertine material is added to the raw materials of the base surface layer. The travertine material is a mixture of one or more of calcium salts, zirconium silicate, silicon carbide and organic particles. The weight percentage of the travertine material in the raw materials of the base surface layer is 0.1% to 10%.

[0011] Further, the raw material of the base layer is made into powder B, and then the powder B is placed in a mold with a beveled edge for pressing to obtain a base layer blank with a beveled edge; the raw material of the base surface layer is made into a powder with a density of 1.60 to 1.75 g / cm 3 The base surface layer slurry is sprayed on the base layer green body to obtain a ceramic green body with a beveled edge portion, and the ceramic green body is fired to obtain a ceramic tile base with a beveled edge portion.

[0012] Furthermore, the raw materials of the base surface layer and the raw materials of the base layer are respectively made into powder A and powder B, powder A is arranged on powder B by stacking cloth, and then pressed with a mold with a beveled edge to obtain a ceramic green body with a beveled edge. After the ceramic green body is fired, a ceramic tile substrate with a beveled edge is obtained.

[0013] Furthermore, the specifications of the sandpaper or grinding wheel are selected from one or more combinations of 20 mesh, 40 mesh, 80 mesh, 120 mesh, and 200 mesh.

[0014] Beneficial effects of the present invention: First, the thickness of the base layer is 0.1 to 3 mm, which is relatively small and mainly serves as the bearing layer of the decorative layer; the water absorption rate of the selected base layer is 0.1% to 6%. Due to the high water absorption rate of the base layer, there are many micropores or cracks inside and on the surface; after grinding and wire drawing the surface of the ceramic tile substrate with sandpaper or grinding wheel, more micropores or cracks can be opened, so that the surface of the base layer has a large number of open micropores or cracks, so that the ceramic ink can be better absorbed, so that the ceramic ink penetrates into the base layer, and after the solvent in the ceramic ink evaporates, the colorant in the ceramic ink is embedded in these micropores or cracks. In the process, the decorative layer and the base layer are organically combined into one, which has very good stability and will not wrinkle or fall off during use; and the ceramic ink can also form a rendering effect in which the color gradually fades during the penetration process, so that the decorative layer has the warm and soft texture of natural materials; when the water absorption rate of the base layer is low, the rendering effect formed by the penetration of the ceramic ink in the base layer is weaker, and when the water absorption rate of the base layer is high, the rendering effect formed by the penetration of the ceramic ink in the base layer is stronger. Therefore, the appropriate ceramic material can be selected according to the rendering effect of the designed decorative layer to achieve the design purpose.

[0015] Secondly, the water absorption rate of the selected base layer is 0.01% to 7%. In this way, ceramic materials with different water absorption rates can be selected according to the quality requirements of the product. It is possible to produce porcelain tiles with extremely low water absorption rate suitable for living rooms, stoneware tiles suitable for bathrooms, and stoneware tiles suitable for outdoor walls. In this way, the selection range of raw materials for the base layer is very broad, which also makes the ceramic tile products of the present invention have a very rich product variety and a very wide range of applications. And when the water absorption rate of the base layer is high, the base layer can also choose the same ceramic material as the base surface layer, thereby further reducing the production cost.

[0016] In addition, the protective layer can also be embedded in the open micropores or cracks on the surface of the base surface layer, so that the protective layer can also be firmly attached to the base surface layer, greatly enhancing the stability and durability of the protective layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a microscopic diagram of the ceramic tile product of the present invention. Figure 1 .

[0018] Figure 2 This is a microscopic diagram of the ceramic tile product of the present invention. Figure 2 .

[0019] Figure 3 It is a macroscopic schematic diagram of the ceramic tile product of the present invention with a serrated texture.

[0020] Figure 4 It is a macroscopic schematic diagram of the ceramic tile product of the present invention with pits and protrusions.

[0021] Figure 5 This is a product photo of the ceramic tile product of Example 1 of the present invention.

[0022] Figure 6 This is an enlarged view of the surface texture of the ceramic tile product of Example 1 of the present invention.

[0023] Figure 7 This is a product photo of the ceramic tile product of Example 2 of the present invention. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is clearly and completely described below in conjunction with the accompanying drawings of the present invention.

[0025] like Figure 1 , 2As shown, the present invention provides a ceramic tile product, including a ceramic tile substrate 1, a decorative layer 2 and a protective layer 3 stacked in sequence from bottom to top. In order to achieve the purpose proposed by the present invention, the ceramic tile substrate 1 includes a base surface layer 12 and a base layer 11 stacked up and down, the base surface layer 12 has a water absorption rate of 0.1% to 6%, the base layer 11 has a water absorption rate of 0.01% to 7%, and the base surface layer 12 has a thickness of 0.1 to 3 mm; the surface of the base surface layer 12 is distributed with a plurality of micropores 13 or cracks 14 with a diameter of 10 to 3000 μm, and the decorative layer 2 covers the base surface layer 12 and is embedded in the micropores 13 or cracks 14.

[0026] In the present invention, the base surface layer 12 is placed on the base layer 11, so the base layer 11 will not be exposed to the outside, so the requirements for raw materials are low, and various waste recycled materials can be used, which greatly reduces the production cost; in addition, the decorative layer 2 does not need to be fired again at high temperature, so there is no problem of colorant discoloration at high temperature, which not only reduces the requirements for ink temperature resistance and reduces costs, but also makes the color selection of ink greater, so that richer color patterns can be formed; the ceramic tile substrate 1 is a fired ceramic material, which has a stable structure and is not easy to deform, so that the pattern texture of the decorative layer 2 is not easy to deform. In this way, when multiple continuous-pattern bricks are laid, the texture docking can be made more precise, presenting a more natural decorative effect, which is easier to obtain the recognition of designers, so that the product can be used in the decoration of high-end places, greatly improving the added value of the product and creating more profits for the company.

[0027] like Figure 3 As shown, the surface of the base layer 12 is also provided with a serrated texture 17. The serrated texture 17 can be formed by grinding or drawing the surface of the base layer with sandpaper or a grinding wheel. On the one hand, the serrated texture 17 can simulate the texture of natural materials, which is closer to natural materials in terms of vision and touch; on the other hand, the serrated texture 17 can also open the micropores or cracks on the surface of the base layer 12 during the processing, so that the surface of the base layer has a rich open micropore or crack structure, achieving multiple goals at one stroke; in addition, the serrated texture 17 can also scatter light, thereby creating a softer visual effect, which will not irritate the eyes, and thus bring a more comfortable visual sense; the decorative layer 2 and the protective layer 3 are embedded in the serrated texture 17, which greatly increases the contact area between the decorative layer 2 and the base layer 12, and between the decorative layer 2 and the base layer protective layer 3, thereby facilitating the adhesion between each other, and improving the stability and durability of the decorative layer 2 and the protective layer 3.

[0028] like Figure 1 , 2As shown, the edge of the ceramic tile substrate 1 is also provided with a bevel portion 4, so that the pattern on the bevel portion 4 can be connected with the pattern on the surface of the ceramic tile substrate 1, so as to achieve a technical effect of consistent internal and external textures like natural materials, thereby overcoming the technical problem of white stubble exposed at the chamfer of ceramic tiles in the prior art; preferably, the bevel portion 4 is arranged on the base surface layer 12, so that the decorative layer 2 on the bevel portion 4 can also be embedded in the base surface layer 12, so that it is not easy to fall off.

[0029] The present invention also provides a method for preparing the above-mentioned ceramic tile products, comprising the following steps: S1: selecting fired ceramic materials as ceramic tile substrates; S2: grinding and drawing the surface of the ceramic tile substrate using sandpaper or a grinding wheel to open the micropores or cracks on the surface of the ceramic tile substrate; S3: inkjet printing on the surface of the ceramic tile substrate using ceramic ink to form a decorative layer; S4: applying a protective layer with a thickness of 5 to 300 μm on the surface of the decorative layer; in order to achieve the purpose of the present invention, the ceramic tile substrate has a base surface layer and a base layer, the water absorption rate of the base surface layer is 0.1% to 6%, and the thickness is 0.1 to 3 mm; the water absorption rate of the base layer is 0.01% to 7%. Preferably, the water absorption rate of the base surface layer is 0.1% to 0.45% or 3% to 6%.

[0030] In the present application, both the base surface layer and the base layer are made of raw materials commonly used in the ceramic industry. Preferably, the raw materials of the base surface layer are formulated by weight to include: 30-70 parts of feldspar, 5-15 parts of quartz, and 5-30 parts of clay. Requirements can be directly made to ceramic manufacturers, who can use existing ceramic tile raw material formulas and production methods to prepare ceramic tile substrates that meet the above requirements.

[0031] Furthermore, the existing ceramic tile raw material formula and firing conditions can also be screened, and raw material A and raw material B with a firing temperature difference of 5 to 30°C are selected to make the base surface layer and the base layer respectively, and fired at a temperature of 1100-1250°C. It is preferred that the firing temperature is consistent with the firing temperature of the base layer, so that the base layer can be well sintered during the firing stage, thereby preparing a base layer with high density and high structural strength, thereby making the structural strength of the entire ceramic tile product better; at the same time, the base surface layer is in an incompletely sintered or over-fired state, so that the base surface layer is The base layer has a higher porosity, which makes it have a higher water absorption rate; this is because when the firing temperature is lower than the firing temperature of the base layer, the base layer is at the end of the oxidation stage, and a large amount of gas is retained inside the base layer, so that the base layer can have more micropores or cracks, and the base layer can have a higher water absorption rate and adsorption; when the firing temperature is higher than the firing temperature of the base layer, the base layer is in an over-burned state, the base layer expands in volume, and the porosity gradually increases, which also makes the base layer have more micropores or cracks, and has a higher water absorption rate and adsorption. In the production of ceramic tiles, the formula and firing temperature have a direct impact on the water absorption rate of the product. The above method can quickly screen out the appropriate raw material formula for the base layer and the base layer, as well as the firing conditions of the ceramic tile matrix.

[0032] In addition, preferably, the thickness of the base layer is 2% to 50% of the overall thickness of the ceramic tile substrate, so that the porous structure of the base layer has less effect on the strength of the overall ceramic tile substrate, thereby making the entire ceramic tile substrate have better mechanical strength.

[0033] Preferably, the raw materials of the base surface layer also include 0.1 to 10 parts of travertine material; wherein the travertine material is a mixture of one or more of calcium salt, silicon carbide, and zirconium silicate. These travertine materials will release gas during the firing process, thereby forming holes of different sizes inside or on the surface of the base surface layer, so that the base surface layer has a higher water absorption rate, thereby further increasing the permeability of the ceramic ink on the base surface layer, making the decorative layer more solid; preferably, the travertine material is ground separately and made into travertine powder, and then mixed with other raw materials of the base surface layer. In order to enrich the number of micropores in the base surface layer, the particle size distribution of the travertine powder is preferably >5 (wt)% under 325 mesh sieve; zirconium silicate can not only release oxygen by pyrolysis at high temperature to produce pores in the base surface layer, but also increase the whiteness of the base surface layer, thereby enhancing the color development effect of the decorative layer; preferably, the weight ratio of zirconium silicate in the raw materials of the base surface layer is 0.1 to 1 part.

[0034] Further, the raw material of the base layer is first prepared into powder B, and the powder B is placed in a mold with a beveled edge for pressing to obtain a base layer blank with a beveled edge; then the raw material of the base surface layer is made into a powder with a density of 1.60 to 1.75 g / cm 3The base surface layer slurry is sprayed on the base layer green body to obtain a ceramic green body with a beveled edge. Figure 2 As shown, this method is suitable for the case where the base layer is thin, such as the case where the base layer thickness is less than 0.5 mm. Since the bevel portion is located on the base layer, the decorative layer of the bevel portion can also be firmly attached to the base layer, thereby having a very high stability.

[0035] The present invention can also prepare the raw materials of the base surface layer and the base layer into powder A and powder B respectively, arrange powder A on powder B by stacking materials, and then press them with a mold with a beveled edge to obtain a ceramic body with a beveled edge. Figure 1 As shown, this method is suitable for the case where the base layer is thicker, such as the case where the base layer thickness is greater than 0.5 mm.

[0036] Furthermore, the mold can also be a mold with texture patterns; the texture patterns are one or more of woven patterns, wood patterns, crack patterns, and water patterns. Then, sandpaper or a grinding wheel is used to perform grinding and wire drawing along the texture patterns to prepare ceramic tile products that are highly simulated in both visual and tactile senses.

[0037] like Figure 4 As shown, the mold can also be a mold with convex or concave parts, so that a ceramic body with pits or protrusions on the surface can be prepared. The pits can simulate the holes on the wood, and the protrusions can simulate the knots of the wood, so as to prepare wood-grain ceramic tile products such as ship wood with a sense of vicissitudes. The pits are preferably smaller than 3mm, and the protrusions are preferably smaller than 1.5mm.

[0038] The sandpaper or grinding wheel is selected from one or more combinations of 20 mesh, 40 mesh, 80 mesh, 120 mesh, and 200 mesh, so as to obtain various styles of rough or delicate ceramic tile products. Preferably, multiple combinations are used, for example, 20 mesh → 80 mesh → 120 mesh → 200 mesh sandpaper or grinding wheel are used in sequence, so that the scratches of 20 mesh coarse sandpaper or grinding wheel are deeper, which can open the closed micropores deeper in the base surface layer, and then 80 mesh, 120 mesh, and 200 mesh sandpaper or grinding wheel are used in sequence to polish the surface of the base surface layer to improve the tactile quality of the product.

[0039] Many existing coatings can be quickly cured by EB curing technology after adding photoinitiators. When the protective layer of the present invention is cured by EB curing technology, the process conditions are: the energy of the electron accelerator is 20-100 KeV, and the curing time is 0.1-5s. Since the electron beam cured coating has strong yellowing resistance, wear resistance and thermal repairability, the electron beam cured coating is used as a protective layer, so that the decorative layer can be used for a long time and keep the color bright, so it is more suitable for desktops, walls, and floor decoration. The electron beam curing device has a large investment and high production efficiency, and is suitable for large-scale production.

[0040] The protective layer coating of the present invention can also be selected from organic hybrid silica sol coating or organic hybrid aluminum sol coating. In this case, the curing conditions of the protective layer are: drying temperature 80-200°C, drying time 5-30 minutes. Organic hybrid silica sol coating or organic hybrid aluminum sol coating can overcome the chemical instability and thermal instability of organic coatings, as well as the defects of easy brittle cracking and poor mechanical properties of inorganic coatings. It has the characteristics of high hardness, not easy to crack, strong anti-aging ability, etc. Using organic hybrid silica sol coating or organic hybrid aluminum sol coating as a protective layer can also make the decorative layer use for a long time and keep the color bright, so it is more suitable for wall and desktop, and can also be used on the ground. The curing device of organic hybrid silica sol coating or organic hybrid aluminum sol coating has low investment and low production efficiency, which is suitable for small-scale personalized customization.

[0041] The present invention will be further described below in conjunction with specific embodiments. Embodiment 1

[0042] In this embodiment, the raw materials of the base surface layer are composed of 35 parts of potassium feldspar, 10 parts of sodium feldspar, 8 parts of quartz sand, 20 parts of kaolin, 5 parts of bentonite, 15 parts of calcite, 4 parts of calcite, 2 parts of silicon carbide, and 1 part of zirconium silicate in terms of weight ratio. The sintering temperature of the base surface layer is 1140°C.

[0043] The raw materials of the base layer are composed of 35 parts of potassium feldspar, 20 parts of sodium feldspar, 3 parts of quartz sand, 18 parts of kaolin, 20 parts of bentonite and 4 parts of wollastonite in terms of weight ratio. The sintering temperature of the base layer is 1160°C.

[0044] The steps for preparing the ceramic brick product in this embodiment are as follows: The first step: ceramic body preparation, the raw materials of the base layer are prepared into powder B by grinding, slurrying, spray granulation and other preparation methods commonly used in the ceramic industry; 35 parts of potassium feldspar, 10 parts of sodium feldspar, 8 parts of quartz sand, 20 parts of kaolin, 5 parts of bentonite, and 15 parts of calcined talc in the raw materials of the base surface layer are also first prepared into powder C by grinding, slurrying, spray granulation and other preparation methods commonly used in the ceramic industry. In order to make the base surface layer have abundant pores inside and on the surface after firing, the particle gradation of powder C is preferably 60 mesh sieve upper material> 80 (wt)%; the travertine material in the raw materials of the base surface layer: 4 parts of calcite, 2 parts of silicon carbide, and 1 part of zirconium silicate are prepared into travertine powder by grinding, slurrying, spray granulation and other preparation methods commonly used in the ceramic industry, and the particle gradation of the travertine powder is 325 mesh sieve> 5 (wt)%; and the travertine powder and powder C are evenly mixed to prepare powder A.

[0045] Step 2: Powder A and powder B are layered in proportion, and then pressed with a mold with a beveled edge to obtain a ceramic body with a beveled edge, such as Figure 1 As shown, the bevel portion is located on the base surface layer; in the ceramic body, the thickness of the base surface layer is 2 mm, the thickness of the base layer is 10 mm, and the height of the bevel portion is 1 mm.

[0046] Step 3: After the ceramic body is dried, it is sent into a kiln for firing to obtain a ceramic tile matrix, the firing temperature is 1160° C., and the firing time is 50 to 55 minutes. After firing, the water absorption rate of the base layer is detected to be 0.1%.

[0047] Step 4: grinding and drawing the surface of the ceramic tile substrate. In this embodiment, the grinding treatment of the ceramic tile substrate surface adopts a stone drawing machine to draw the surface of the ceramic tile substrate along the length direction of the ceramic tile substrate. In this way, the pore walls on the surface of the base layer can be ground off, so that the surface of the base layer has abundant open micropores or cracks, such as Figure 6 As shown, the diameter of these open micropores or cracks is measured to be 50-3000μm, and there are also large holes with a diameter of 5-10mm; the base surface layer also has a serrated water pattern texture to simulate the serrated marks left on the stone surface when the stone is cut. In this example, the sandpaper of the stone drawing machine uses 20 mesh, 40 mesh, and 80 mesh specifications in turn to grind and draw the surface of the ceramic tile substrate to obtain a relatively rough texture. The water absorption rate of the base surface layer is tested to be 5.0%.

[0048] Step 5: Inkjet printing of the decorative layer. In this embodiment, an inkjet printer and ceramic ink commonly used in the ceramic industry are used for inkjet printing to form a decorative layer with natural stone water patterns on the surface of the base layer and the surface of the bevel. The ceramic ink is preferably an inorganic pigment ceramic ink, which is low in cost, rich in color, and has good heat and light resistance and is not easy to fade. The drying of the decorative layer is preferably carried out by a natural drying method, so that the ceramic ink dries more slowly, so that it can more fully penetrate into the base layer to form a more solid decorative layer.

[0049] Step 6: Spray the protective layer. Many existing coatings can be quickly cured by EB curing technology after adding photoinitiators. This application uses bisphenol A epoxy resin 618 as the raw material for the protective layer, and adds 1% of the resin weight of the photoinitiator. The photoinitiator selected is GE's (4-octylphenoxy) phenyl iodine hexafluoroantimonate (OPPI); the above coating is applied to the decorative layer by spraying, and then cured by electron beam curing technology; the electron beam curing process conditions used are as follows: the energy of the electron accelerator is 110KeV, the curing time is 0.1s, the radiation dose is 60KGy, and the thickness of the protective layer is 25 microns.

[0050] like Figure 5 , 6 As shown, the surface of the ceramic tile product produced in this embodiment has the hole structure of natural travertine, and a natural stone texture with water flow patterns is formed on the base surface layer by inkjet printing, and the texture of the water flow patterns also has a relatively rough serrated structure; the texture of the surface and the bevel of the ceramic tile product produced is consistent.

[0051] The microscopic diagram of the ceramic brick product of this embodiment is as follows: Figure 1 As shown, this embodiment is suitable for the case where the base surface layer is thicker, especially for the case of imitating natural travertine bricks. Embodiment 2

[0052] The steps and parameters in this embodiment are the same as those in Embodiment 1, except that: ① When grinding and brushing the surface of the ceramic tile substrate, use sandpapers of 20 mesh, 40 mesh, 80 mesh, 120 mesh and 200 mesh in turn; first, use 20 mesh sandpaper or grinding wheel to grind and brush the surface of the ceramic tile substrate to open the micropores or crack structure on the surface of the base layer, so that the surface of the base layer has abundant open micropores or cracks, which is further conducive to the ceramic ink to penetrate into the base layer and combine with the base layer as a whole, thereby enhancing the stability of the decorative layer; then use 40 mesh, 80 mesh, 120 mesh and 200 mesh sandpaper to grind and brush the surface of the ceramic tile substrate in turn to obtain ceramic tile products with a delicate surface touch.

[0053] ② The pattern and color of inkjet printing in this embodiment are slightly different from those in Example 1.

[0054] ③ In this embodiment, the protective layer coating used is an organic hybrid aluminum sol coating. The transparent aluminum sol (Model CY-BZ10) of Hangzhou Jiupeng New Materials Co., Ltd. is selected as the protective layer coating. The above-mentioned organic hybrid aluminum sol is applied to the surface of the ceramic tile substrate by roller coating. The thickness of the protective layer is 20μm, and the curing conditions of the protective layer are temperature 80°C and time 10 minutes.

[0055] This example is prepared as Figure 7 Ceramic tile products shown. Embodiment 3

[0056] The steps and parameters in this embodiment are the same as those in Embodiment 1, except that: ① The composition of the raw materials of the base surface layer in weight ratio is: 35 parts of potassium feldspar, 15 parts of sodium feldspar, 12 parts of quartz sand, 12 parts of kaolin, 18 parts of pyrophyllite, 7 parts of calcined talc, and 1 part of zirconium silicate; during preparation, 35 parts of potassium feldspar, 15 parts of sodium feldspar, 12 parts of quartz sand, 13 parts of kaolin, 18 parts of pyrophyllite, and 7 parts of calcined talc are first mixed together, and powder C is prepared through grinding and slurrying and spray granulation commonly used in the ceramic industry, and then 1 part of zirconium silicate powder with a particle size of less than 325 mesh is added to powder C, and powder A is obtained after stirring evenly; the firing temperature of the base surface layer is 1210°C.

[0057] ② The composition of the raw materials of the base layer by weight is: 40 parts of ceramic waste recycled materials, 25 parts of feldspar, 15 parts of quartz sand, and 20 parts of kaolin tailings; the firing temperature of the base layer is 1180° C. After firing, the water absorption rate of the base layer is tested to be 4.0%.

[0058] ③ Use a mold with a wood grain texture to press the ceramic body to obtain a ceramic tile body with a wood grain texture.

[0059] ④ Send the ceramic body into the kiln for firing to obtain a ceramic tile matrix. The firing temperature of the kiln is 1180°C and the firing time is 50 to 55 minutes.

[0060] ⑤ Use sandpaper with mesh sizes of 20, 80, 120 and 200 in sequence to grind and brush the surface of the ceramic tile substrate along the direction of the wood grain.

[0061] ⑥ The protective layer coating used in this embodiment is an organic hybrid silica sol coating, and the transparent silica sol (model CY-S01) of Hangzhou Jiupeng New Materials Co., Ltd. is selected as the protective layer coating; the protective layer coating is applied to the surface of the ceramic tile substrate by roller coating, the thickness of the protective layer is 20 microns, and the protective layer curing conditions are temperature 80°C and time 8 minutes.

[0062] In this embodiment, the firing temperature is lower than the firing temperature of the base surface layer. Therefore, during the firing process, the base surface layer is in the late oxidation stage and a large amount of liquid phase has not yet formed, so that a large amount of pore structure can be retained. After firing, these pore structures make the base surface layer have abundant pores. After grinding or wire drawing, the surface of the base surface layer has abundant open micropores or crack structures. The water absorption rate of the base surface layer of this embodiment is tested to be 0.3%, and the diameter of the open micropores or cracks on its surface is 10-100μm.

[0063] In this example, since a large amount of waste recycled materials are used, the raw material cost of the base layer is relatively low, which is conducive to reducing production costs. Embodiment 4

[0064] In this embodiment, the steps and parameters are the same as those in the third embodiment, except that: ① The raw materials of the base layer are first prepared into powder B by grinding, pulping, spray granulation and other preparation methods commonly used in the ceramic industry; the powder B is pressed by a mold with a wood grain texture to obtain a base layer body.

[0065] ② First, mix 35 parts of potassium feldspar, 25 parts of sodium feldspar, 10 parts of quartz sand, 10 parts of kaolin, and 15 parts of calcined talc in the base surface layer raw materials, and then grind them into a preliminary slurry. The fineness of the preliminary slurry is 0.5% of the residue on the 325 mesh sieve and the density is 1.65g / cm 3 ; Then add 1 portion of zirconium silicate powder with a particle size of less than 325 mesh into the preliminary slurry and mix evenly to form a base layer slurry; apply the above base layer slurry on the base layer body by spraying to obtain a ceramic body, and the base layer thickness is 0.5 mm.

[0066] Since the fineness of the base surface layer slurry is smaller, the density of the base surface layer after firing is higher than that of Example 3. After testing, the diameter of the surface opening micropores of the base surface layer in this embodiment is 10-50μm, and the water absorption rate is 0.2%.

[0067] The microscopic diagram of the ceramic brick product of this embodiment is as follows: Figure 2 As shown, this embodiment is suitable for the case where the base surface layer is thin.

[0068] The ceramic tile products prepared in Examples 1, 2, 3 and 4 were subjected to multiple illumination tests to observe the states of the decorative layer and the protective layer. The illumination test conditions were: test temperature 38°C, humidity 50%, and illumination intensity 50W / m 2 (300~400nm), test time 1000h / time.

[0069] The status of the decoration layer after multiple lighting test experiments is shown in the following table: sample A lighting test Secondary lighting test Three lighting tests Embodiment 1 No peeling or cracking No peeling or cracking No peeling or cracking Embodiment 2 No peeling or cracking No peeling or cracking No peeling or cracking Embodiment 3 No peeling or cracking No peeling or cracking No peeling or cracking Embodiment 4 No peeling or cracking No peeling or cracking No peeling or cracking In the present invention, since the base surface layer has abundant open micropores or cracks, the protective layer can also be embedded in these open micropores or cracks, so the protective layer of the present invention also has very good firmness. It can be seen from the above table that the ceramic tile product of the present application, the decorative layer and the protective layer are very stable, which can well solve the technical problems existing in the prior art.

Claims

1. A ceramic tile product, comprising a ceramic tile substrate (1), a decorative layer (2) and a protective layer (3) stacked in sequence from bottom to top, characterized in that: The ceramic tile substrate (1) comprises a base surface layer (12) and a base layer (11) stacked up and down, the base surface layer (12) has a water absorption rate of 0.1% to 6%, the base layer (11) has a water absorption rate of 0.01% to 7%, and the base surface layer (12) has a thickness of 0.1 to 3 mm; the surface of the base surface layer (12) is provided with a plurality of micropores (13) or cracks (14) with a diameter of 10 to 3000 μm, and the decorative layer (2) covers the base surface layer (12) and is embedded in the micropores (13) or cracks (14).

2. The ceramic tile product according to claim 1, characterized in that: The surface of the base surface layer (12) is also provided with a sawtooth texture pattern (17).

3. The ceramic tile product according to claim 1, characterized in that: The ceramic tile base (1) is also provided with a bevel portion (4) at the edge thereof, and the bevel portion (4) is located on the base surface layer (12).

4. A method for preparing a ceramic tile product according to any one of claims 1 to 3, comprising the following steps: S1: selecting fired ceramic material as a ceramic tile matrix; S2: grinding and brushing the surface of the ceramic tile substrate using sandpaper or a grinding wheel to open the micropores or cracks on the surface of the ceramic tile substrate; S3: using ceramic ink to inkjet print on the surface of the ceramic tile substrate to form a decorative layer; S4: applying a protective layer with a thickness of 5 to 300 μm on the surface of the decorative layer; Features: The ceramic tile substrate comprises a base surface layer and a base layer. The water absorption rate of the base surface layer is 0.1% to 6% and the thickness is 0.1 to 3 mm. The water absorption rate of the base layer is 0.01% to 7%.

5. The preparation method according to claim 4, characterized in that: The coating used for the protective layer is a coating that can be cured by EB curing technology. After the protective layer coating is applied to the decorative layer by spraying or roller brushing, the protective layer coating is cured by EB curing technology to form a protective layer. The operating process conditions of the EB curing technology are: the energy of the electron accelerator is 20 to 100 KeV, and the curing time is 0.1 to 5 s.

6. The preparation method according to claim 4, characterized in that: The coating used for the protective layer is an organic hybrid nano-silica sol coating or an organic hybrid nano-aluminum sol coating. After the protective layer coating is applied to the decorative layer by spraying or roller brushing, the protective layer coating is cured by heating and drying to form a protective layer. The heating and drying curing process conditions are: temperature 80-200°C, drying time 5-30 minutes.

7. The preparation method according to claim 4, characterized in that: Travertine material is also added to the raw materials of the base surface layer. The travertine material is a mixture of one or more of calcium salts, zirconium silicate, silicon carbide and organic particles. The weight proportion of the travertine material in the raw materials of the base surface layer is 0.1 to 10 parts.

8. The preparation method according to claim 4, characterized in that: The raw material of the base layer is made into powder B, and then the powder B is placed in a mold with a beveled edge for pressing to obtain a base layer blank with a beveled edge; the raw material of the base surface layer is made into a powder with a density of 1.60 to 1.75 g / cm 3 The base surface layer slurry is sprayed on the base layer green body to obtain a ceramic green body with a beveled edge portion, and the ceramic green body is fired to obtain a ceramic tile base with a beveled edge portion.

9. The preparation method according to claim 4, characterized in that: The raw materials of the base surface layer and the base layer are made into powder A and powder B respectively, powder A is arranged on powder B by stacking cloth, and then pressed with a mold with a beveled edge to obtain a ceramic green body with a beveled edge. After the ceramic green body is fired, a ceramic tile substrate with a beveled edge is obtained.

10. The preparation method according to claim 4, characterized in that: The specifications of the sandpaper or grinding wheel are selected from one or more combinations of 20 meshes, 40 meshes, 80 meshes, 120 meshes, and 200 meshes.

Citation Information

Patent Citations

  • Method for producing outer rounded tile and outer rounded tile

    CN115335580A

  • Ink-jet printing unfired decorative lightweight ceramic plate and preparation method thereof

    CN115745665A

  • One-time sintering glass-ceramic composite board and preparation method thereof

    CN103224403A

  • Outer wall stone-simulated decorative plate and manufacturing method thereof

    CN103469986A

  • Method for preparing inkjet-penetrated travertine polished tiles

    CN105541343A